SPONTANEOUS UTERINE RUPTURE DURING PREGNANCY - Cerović Popović, Radojka; Sparić, Radmila (Srpski medicinski časopis Lekarske komore, 2023)
Uterine rupture is a life-threatening complication of pregnancy which is associated with high incidence rates of maternal and neonatal morbidity and mortality. The aim of this paper is to present the risk factors, clinical picture, and diagnostic and therapeutic options for the management of uterine rupture. The paper presents the data from the papers selected by searching the PubMed database using the combination of the following keywords: uterine rupture, pregnancy, delivery, risk factors, diagnosis, treatment. In developed countries, uterine rupture is most often a complication of a previous caesarean section, and less frequently of other uterine procedures. It occurs more frequently in developing countries, and it is usually the consequence of obstructed labor or inadequate use of labor-inducing medication. A typical clinical picture of uterine rupture includes abdominal pain and hemorrhagic shock in the mother and abnormal fetal heart rate. Non-specific symptoms and signs of uterine rupture make timely diagnosis difficult. The treatment of uterine rupture depends on the extent of the rupture, age, parity, and the patient’s general condition. The primary goal is to stop hemorrhage and make the patient hemodynamically stable, which is done by hysterectomy or suturing of the uterus. Due to the increasing caesarean section rate and the fact that nowadays it is the most common risk factor for uterine rupture during pregnancy and childbirth, uterine rupture is still an important complication of pregnancy. Uterine rupture should be considered in pregnant women with risk factors, especially in case of non-specific abdominal pain and cardiotocographic changes. In such situations, timely diagnosis and immediate treatment can significantly contribute to a favorable maternal and neonatal outcome.